(untitled) (Research, Society and Development, 2021)
Textile industries activities can positively affect a city’s economy. However, those industries require a great deal of water and sheds high organic load into water bodies, causing a considerate environmental impact. As potential pollutant substances, the dye’s presence in textile effluents are recalcitrant and can change the chemical and physical properties. It also resists conventional treatments. The treatment based on advanced oxidation processes presents to be efficient on dye’s degradation, but it may generate secondary toxic compounds, therefore is necessary to use techniques to evaluate its toxicity after the treatment. This study evaluated a laundry effluent, both before and after the treatment using the photo - Fenton processes. Applying liquid chromatography, results have shown that the dye’s degradation was higher than 90% and a COD decrease to 73%.